A Systematic Review of Factors Associated with Post-Sternotomy Pain - Musta’in; Tri Yuniarti; Aris Widiyanto; Hakim Anasulfalah (Masters Program in Public Health, 2026)
Background: Chronic post-sternotomy pain remains an important complication after cardiac surgery. Earlier reviews combined several cardiac surgical approaches and did not incorporate recent sternotomy-specific evidence. This review aimed to identify and critically synthesize demographic, clinical, psychological, surgical, and perioperative factors associated with chronic post-sternotomy pain. Subjects and Method: This systematic review followed PRISMA 2020. BASE, PubMed, and ScienceDirect were searched for English-language studies published from January 2010 to June 2025. The review question used a PECO framework: adults undergoing cardiac surgery through median sternotomy; exposure to potential prognostic factors; comparison with unexposed or lower-risk groups; and chronic post-sternotomy pain at three months or longer. Observational analytic studies were eligible. Risk of bias was assessed with design-specific CASP cohort and CASP case control checklists. Results: Seven studies involving 3,304 participants were included in the narrative synthesis. Greater acute postoperative pain and internal thoracic or mammary artery harvesting showed the most consistent associations, each recurring in three studies. Female sex, pre-existing chronic pain, and depression or related psychological vulnerability were also reported in more than one study. Other factors included younger age, obesity, diabetes mellitus, preoperative angina, previous cardiac surgery or percutaneous coronary intervention, reduced ejection fraction, hypothyroidism, wound complications, non-elective surgery, re-sternotomy, longer hospital stay, and disability or retirement-related medical assessment. Several associations were based on single-centre or unadjusted analyses. Conclusion: Chronic post-sternotomy pain has a multifactorial risk profile. The most consistent evidence supports severe acute postoperative pain and internal thoracic artery harvesting as clinically relevant markers. Preoperative risk assessment and effective early pain control should receive priority, while larger multi-center studies with standardized outcome definitions are needed.